An SSR-SNP Linkage Map of the Parasitic Weed Orobanche cumana Wallr. Including a Gene for Plant Pigmentation - Calderón-González, Álvaro; Pouilly, Nicolas; Muños, Stéphane; Grand, Xavier; Coque, Marie; Velasco, Leonardo; Pérez-Vich, Begoña (Frontiers in Plant Science, 2019)
Sunflower broomrape (Orobanche cumana Wallr.) is a holoparasitic plant that causes major yield losses to sunflower crops in the Old World. Efforts to understand how this parasitic weed recognizes and interacts with sunflower are important for developing long-term genetic resistance strategies. However, they are hampered by the lack of genetic tools in O. cumana. The objectives of this research were to construct a genetic linkage map of this species using SSR and SNP markers, and mapping the Pg locus that is involved in plant pigmentation. The genetic map was developed from the progenies of a cross between O. cumana inbred lines EK-12 and EK-A1, which originated from populations belonging to two distant and geographically separated gene pools identified in Spain. The inbred lines also differed for plant pigmentation, with EK-A1 lacking anthocyanin pigmentation (pgpg genotype). A genetic map comprising 26 SSR and 701 SNP markers was constructed, which displayed 19 LGs, corresponding to the 19 chromosome pairs of O. cumana. The total length of the map was 1795.7 cM, with an averaged distance between two adjacent positions of 2.5 cM and a maximum map distance of 41.9 cM. The pigmentation locus Pg mapped to LG19 between SNP markers OS02468 and OS01653 at 7.5 and 3.4 cM, respectively. This study constitutes the first linkage map and trait mapping study in Orobanche spp., laying a key foundation for further genome characterisation and providing a basis for mapping additional traits such as those having a key role in parasitism.